Our Palace of Intestines: An Art Project-in-Progress - Couch, Amanda (Cuizine, 2018)
Our Palace of the Intestines was the final part of a workshop, Extispicy in the Everyday: An Exploration of Human-Environment Binaries through the Gut, delivered at the 9th Society of Artistic Research conference, “Artistic Research Eats Itself” at the University of Plymouth, England, on April 11, 2018. It performs multiple acts of inter-embodiment and engages with live audience-participants.